2015
DOI: 10.15376/biores.11.1.1270-1279
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for the Production of Pure Crystalline Silica from Lemon Grass

Abstract: Lemon grass is an inexpensive raw material that can be used to produce natural silica. A method using hydrochloric acid (HCl) leaching followed by thermal combustion at 600 °C was developed to produce purified silica from lemon grass. Acid leaching temperatures of 33, 50, 80, and 110 °C were used. The silica content of the lemon grass ash was characterized using X-ray fluorescence (XRF), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared (FTIR) analysis. The shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…1, 2, 3). Earlier reports revealed that the amorphous form of silica is usually pure and has small particle size and high surface area [14]. The present study showed that the treated ash obtained from all the three (Fig.…”
Section: Chemical Composition Of Plant Extractssupporting
confidence: 66%
See 1 more Smart Citation
“…1, 2, 3). Earlier reports revealed that the amorphous form of silica is usually pure and has small particle size and high surface area [14]. The present study showed that the treated ash obtained from all the three (Fig.…”
Section: Chemical Composition Of Plant Extractssupporting
confidence: 66%
“…The leaf, stem and root of C. flexuosus were collected and washed to remove impurities and further dried at 105 °C for 24 h. The samples were soaked separately in 5 M HCl at different temperatures of 40-100 °C for 3 h. The acidtreated samples were rinsed with distilled water thrice and dried in oven at 105 °C for overnight. The dried samples were calcined at 600 °C until it turned to white ash [14].…”
Section: Extraction Of Silica By Acid Leachingmentioning
confidence: 99%
“…1, 2, 3). Earlier reports revealed that the amorphous form of silica is usually pure and has small particle size and high surface area [14]. The present study showed that the treated ash obtained from all the three parts of C. flexuosus contained predominantly silica particles and no original compounds were observed.…”
Section: Chemical Composition Of Plant Extractssupporting
confidence: 53%
“…The spectra obtained are displayed in spectra a−c of Figure 2, which show numerous adsorption bands. The weak bands observed in spectra a and b of Figures 2 at 3200−3300 cm −1 are assigned to the strong H−OH stretch or Si−OH, 43 while bands at 1654, 1396, 1200, and 1122 cm −1 are assigned to carbonate C−O stretching and bending vibrations, 19 which suggest the presence of carbonate. The band at about 1396 cm −1 is distinct for K 2 CO 3 .…”
Section: Resultsmentioning
confidence: 98%